MRI Study and Psychological Assessment in Children and Youth with Deviation Behaviour - Khachidze, Irma; Gogotishvili, Tea; Nadirashvili, Dimitri; Kapanadze, Nana; Alaverdashvili, Mariam (Journal of Psychological Disorders, 2019)
Objective Antisocial behavior (ASB) in children and youth is public health problem in Georgia. Nevertheless, there has been no systematic study the risk factors for ASB that could counteract on ASB development. To prevent ASB development and acceleration the understanding of biological (assessment of Brain morphology using MRI) and psychological (assessment using Freiburg Personality Inventory) risk factors is critical. This was the aim of this study. Method The children/youth with ASB tendency (AST) were identified by the Freiburg Personality Inventory (FBI). The biological and psychosocial factors contributing to AST were evaluated using a semi-structured clinical interview. Brain anatomy and morphology was studied using magnetic resonance imaging (MRI). Results Children/youth with AST had significant abnormalities in most axial elements of the DSM multi-axial system but not in brain anatomy measured by MRI. Conclusion Early identification of ASB tendencies and a provide correlationship between specific psychiatric, medical and family stress factors will likely reduce the number of children/youth with ASB and will promote their integration into society.
Keywords: MRI; risk factors; neural basis; comorbidity; Antisocial tendency; children; youth